Radio Frequency Source Coding Made Easy - Faruque, Saleh (Springer, 2015)
This book introduces Radio Frequency Source Coding to a broad audience. The author blends theory and practice to bring readers up-to-date in key concepts, underlying principles and practical applications of wireless communications. The presentation is designed to be easily accessible, minimizing mathematics and maximizing visuals.